Pengaruh Kepemilikan Manajerial, Media Visibility dan Umur Perusahaan terhadap Pengungkapan Sustainability Report pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2018 – 2022 - Tyasa, Elvitra Faradea; Taqwa, Salma (Jurnal Nuansa Karya Akuntansi, 2023)
The primary objective of this study is to investigate how sustainability report disclosure is influence by factors such as managerial ownership, media visibility, and the age of the company. The study relies on data extracted from annual and sustainability reports of firms that are publicly listed on the Indonesia Stock Exchange (BEI) during the years 2018 to 2022. The research employs purposive sampling, involving the selection of 45 companies within the 2018-2022 time frame. To test the hypotheses, the study utilizes multiple linear regression analysis. The research findings indicate that managerial ownership significantly enhances sustainability report disclosure, media visibility has no discernible impact on sustainability report disclosure, and company age has a noteworthy positive effect on sustainability report disclosure.